Guidance on the management of left ventricular assist device (LVAD) supported patients for the non‐LVAD specialist healthcare provider: executive summary. (22nd August 2021) - Ben Gal, Tuvia; Ben Avraham, Binyamin; Milicic, Davor; Crespo‐Leiro, Marisa G.; Coats, Andrew J.S.; Rosano, Giuseppe; Seferovic, Petar; Ruschitzka, Frank; Metra, Marco; Anker, Stefan; Filippatos, Gerasimos; Altenberger, Johann; et al.
Abstract: The accepted use of left ventricular assist device (LVAD) technology as a good alternative for the treatment of patients with advanced heart failure together with the improved survival of patients on the device and the scarcity of donor hearts has significantly increased the population of LVAD supported patients. Device‐related, and patient–device interaction complications impose a significant burden on the medical system exceeding the capacity of LVAD implanting centres. The probability of an LVAD supported patient presenting with medical emergency to a local ambulance team, emergency department medical team and internal or surgical wards in a non‐LVAD implanting centre is increasing. The purpose of this paper is to supply the immediate tools needed by the non‐LVAD specialized physician — ambulance clinicians, emergency ward physicians, general cardiologists, and internists — to comply with the medical needs of this fast‐growing population of LVAD supported patients. The different issues discussed will follow the patient's pathway from the ambulance to the emergency department, and from the emergency department to the internal or surgical wards and eventually back to the general practitioner.